Filamin A organizes γ‑aminobutyric acid type B receptors at the plasma membrane - Marie-Lise Jobin; Sana Siddig; Zsombor Koszegi; Yann Lanoiselée; Vladimir Khayenko; Titiwat Sungkaworn; Christian Werner; Kerstin Seier; Christin Misigaiski; Giovanna Mantovani; Markus Sauer; Hans M. Maric; et al. (Nature Communications, 2023)
GABAB receptors mediate the effects of the main inhibitory neurotransmitter in the brain. Here, authors identify the cytoskeletal protein filamin A as a key player that controls the exact location and function of GABAB receptors at the cell surface.